ANALISIS RANTAI NILAI AGROINDUSTRI SUSU BUBUK KEDELAI (Studi Kasus Industri Sumber Gizi Nabati dan Melilea di Kota Pekanbaru) - Hedron Asfira Monzery; Shorea Khaswarina; Novia Dewi (Universitas Riau, 2014)
The objective of study was to analyse value chains and marketing margins from Sumber Gizi Nabati (SGN)and Melilea soybean milk agro-industries. This study was conducted from Februari until Maret 2013. Datacollected were those of primary and secondary data. The methods of study used case studies, while thedetermination of the population is conducted by survey method. The data obtained was analyzed usingdescriptive method, scoring in each indicators, multiple regresi analysis and then analysis of the marketingmargins. Most of respondents drawn from incidental consumersof soybean milk powder with number ofsample from SGN 30 people and Melilea 30 people.The result of this study; the value chain showed thatthere are two activities in a company, the primary activity and the support activity; margin analysis showedthat marketing margin of SGN industry greater than Melilea.Key words : Soybean Milk, Value Chain, Consument